Hydrothermal Signatures Discovered in Outcropping Rocks of the Los Humeros Geothermal Field (Mexico): A Geochemometric Exploration Case Study - D. Yáñez-Dávila; E. Santoyo; E. González-Partida; Kailasa Pandarinath; G. Santos-Raga; Sumit Mishra; Z. G. Gómez-Salgado (Geofluids)
Hydrothermal geochemical signatures in outcropping rock samples of the super-hot Los Humeros geothermal field were discovered by using an integrated geochemometric study of the mobility of components (major oxides) and trace elements. Chemical component and element mobilities were determined by using the Gresens–Grant equation for mass balances. A spatial distribution of component and element mobility patterns was carried out through the mineral characterization, hydrothermal alteration, and whole-rock elemental analysis. Four alteration assemblages were mainly identified: (i) argillic–silicic; (ii) argillic–sericite; (iii) advance argillic–sulphate acid (alunite or jarosite); and (iv) silicic–carbonate. A clear increasing order of mobility for major oxides such as Fe2O3T, P2O5, K2O, MnO, SiO2, CaO, Al2O3, and MgO and trace elements such as Pb, Th, Sr, Zn, V, Rb, Cr, Cu, and Ba was inferred from hydrothermally altered rocks. The mobility of these components and trace elements showed a geochemical association with a higher contribution of Fe2O3T, CaO, V, Cu, Zn, and Sr and a lower contribution of K2O, Rb, Th, and Cr. The spatial distribution of hydrothermal signatures obtained by tracking the mobilities of major and trace elements in samples collected in a new sector of Los Humeros geothermal field is aligned with NW-SE and NE-SW fault systems. Three areas characterised by a higher permeability were identified, for the first time, from low-cost analyses of rock samples by using energy-dispersive X-ray fluorescence spectrometry. The successful application results obtained from this study provided a new integrated geochemometric method to track high permeability zones for geothermal prospection tasks.